Insecticidal effect of eucalyptus and mugwort essential oil against kcona kcona of quinoa cultivation (Revista Ciencia Agraria, 2022)
This research allowed us to evaluate the insecticidal effect of eucalyptus essential oil (Eucalyptus Globulus) and feverfew (Franseria artemisioides) against the kcona kcona (Eurysacca melanocampta) in the cultivation of quinoa (Chenopodium quinoa Willd.). In the development of the process for obtaining oil by steam dragging, the optimal parameters measured were extraction time, temperature and pressure. Characterizing essential oils by gas chromatography coupled to mass spectrometry, where the main components of eucalyptus were Eucalyptol (59.19%), α-Pinene (20.89%) and D-Limonene (6.29%); and mugwort were 5,5-dimethyl-2-ethyl-1,3-Cyclopentadiene (30.65%), β-Himachalene (14.69%) and α-Caryophyllene (10.27%). The physicochemical characterization of density and refractive index of eucalyptus was 0.912 g/mL and 1.4606 respectively, and of mugwort 0.921 g/mL and 1.4857 respectively, performed at 20°C. Regarding the evaluation of the insecticidal activity of the essential oil of eucalyptus and mugwort in the mortality of the Kcona Kcona; the treatments showed effectiveness in controlling the pest. The analysis of variance for the application of eucalyptus essential oil has as optimal values ​​a time of 24 h with a concentration of 1.00%, and mortality of 46.6667%; for the essential oil of mugwort, the optimal values ​​were a time of 24 h with a concentration of 1.00% and mortality of 43.333%.
Keywords: insecticidal activity; steam extraction; kcona kcona; pest; toxic